Clinical and radiographic features of HIV-related pulmonary tuberculosis according to the level of immunosuppression - Garcia,Guilherme Freire (2007)
Medical charts and radiographs from 38 HIV-infected patients with positive cultures for Mycobacterium tuberculosis from sputum or bronchoalveolar lavage were reviewed in order to compare the clinical, radiographic, and sputum bacilloscopy characteristics of HIV-infected patients with pulmonary tuberculosis according to CD4+ lymphocyte count (CD4). The mean age of the patients was 32 years and 76% were male. The median CD4 was 106 cells/mm³ and 71% had CD4 < 200 cells/mm³. Sputum bacilloscopy was positive in 45% of the patients. Patients with CD4 < 200 cells/mm³ showed significantly less post-primary pattern (7% vs. 63%; p = 0.02) and more frequently reported weight loss (p = 0.04). Although not statistically significant, patients with lower CD4 showed lower positivity of sputum bacilloscopy (37% vs. 64%; p = 0.18). HIV-infected patients with culture-confirmed pulmonary tuberculosis had a high proportion of non-post-primary pattern in thoracic radiographs. Patients with CD4 lower than 200 cells/mm³ showed post-primary patterns less frequently and reported weight loss more frequently.